Dynamic Governance dalam Pengelolaan Sampah di Kota Pekanbaru - Nur Maharani Zurima; Hasim As’ari; Abdul Sadad (PUBLICNESS: Journal of Public Administration Studies, 2026)
This research is motivated by the increasing waste problem in Pekanbaru City, which has led to policy changes and institutional reconstruction in its management system. These dynamics require local governments to have adaptive and responsive governance capacity to environmental changes. This study aims to implement dynamic governance in waste management in Pekanbaru City. The research used a qualitative approach with an explanatory case study. Data were obtained through in-depth interviews, policy documentation, and field observations. Analysis was conducted using the concept of dynamic governance from Neo and Chen, which includes indicators of culture, capability, and change. The results show that in the cultural dimension, the value of collaboration is starting to develop, but has not been fully internalized in operational practices. In terms of capability, the ability to think ahead, rethink, and think across the board emerged through policy changes and the establishment of the LPS, but has not been supported by a data-based evaluation system and structured organizational learning. During the change, policy transformation occurred rapidly but was not matched by the readiness of apparatus capacity, cross-institutional coordination, and consistent policy socialization. These findings indicate that dynamic governance in waste management in Pekanbaru City is still in a transition phase towards more adaptive governance.